KESENJANGAN USIA DALAM PERNIKAHAN MENURUT FIQH MUNAKAHAT DI KECAMATAN WARUNGASEM - Apriliani, Ida Fara; Afiyah, Maulida; Hami, Widodo (Islamic Family Law, STAI Sangatta Kutai Timur, 2024)
This research aims to explain the age gap that occurs in marriage. The subjects in this study were husband and wife couples whose ages were more than 8 years apart. Interviews and observations were conducted in October 2023. This research used descriptive qualitative research methods. The aspects discussed in this research are the meaning of marriage itself, the factors that cause the age gap in marriage, and also the impact of this large age difference. The results of this research are that marriages with a large age gap do not affect the household situation becoming strained, even if the husband is more mature, then he will be able to guide his wife and children. Couples who are ready to get married physically and mentally are also expected to have a prosperous and quality family.